Technical Note: Anaerobic thread compound used on large diameter casing completed as a recoverable gas tight tubing string in cavern wells. (4th August 2014) - Vincent, L.; Hooks, J.; Robbins, R.; Boutwell, D.
Cavern wells have their unique problems. Anaerobic technology has been used in various industries over the past 30 years. A special formulation has recently been developed to satisfy the unique needs of OCTG application. This Note descibes the development of an anaerobic sealant for oil field tubular connections and outlines actual field application and running procedures.